The Effect of Using Black Tea as an Alternative Diuretic on Multislice Computed Tomography (MSCT) Urography Examination - widyasari, dina; Choridah, Lina; Ardiyanto, Jeffry (Universitas 'Aisyiyah Yogyakarta, 2023)
The MSCT urography examination requires patient preparation, such as fasting and drinking water.In addition,some hospitals use water,furosemide to accelerate the increase in urine volume.However,Furosemide is a chemical diuretic that is feared to increase the workload of the kidneys. So a natural alternative is needed, namely black tea.This study aims to determine the effect of black tea as an alternative diuretic on the urography MSCT examination. This is quasi-experimental research conducted at RSUD by Dr. Soehadi Prijonegoro Sragen,Central Java. Respondents in this study consisted of 18 outpatients with an MSCT urography examination. These respondents were divided into three groups, namely the group of mineral water, furosemide,and black tea, and three radiology doctors. The scanning process uses MSCT 128 Slice and then tracks MSCT urography with the Curved Multiplanar Reconstruction (MPR) application.Data obtained from observations,questionnaires,and interviews with radiologists was then processed and analyzed using quantitative methods.Normal distributed data was analyzed using the ANOVA test. The results showed a significant difference from the assessment of kidney HU,liver HU, and ureteral dilatation in the mineral water, furosemide, and black tea test groups with sig values.<0.05.Black tea increases Hounsfield Unit (HU) values in the kidneys,lungs,liver,and ureteral dilation, as a tracking picture shown in the Curved Multiplanar Reconstruction(MPR) application. This confirms that black tea can be used as a natural diuretic alternative for some reasons:effective, fast, easy, and inexpensive.It makes it easier to track kidney stones.The operation of curved multiplanar reconstruction(MPR) applications during reconstruction can display more optimal image results to support more accurate diagnostic information.